Oral Presentation No. 53 Dose-related preprocedural patency of the infarct-related artery after zalunfiban (RUC-4) administration upon arrival at the catheterization laboratory in ST-elevation myocardial infarction: insights from the phase IIa study. (21st October 2022) - Rikken, Sem A O F; Bor, W L; Zheng, K L; Gibson, C M; Granger, C B; Coller, B S; Bentur, O; Lobatto, R; Postma, S; Van 't Hof, A W J; Ten Berg, J M
Abstract: Background: The importance of time to reperfusion after ST-elevation myocardial infarction (STEMI) is well established. Pre-hospital use of glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors improves pre-percutaneous coronary intervention (PCI) perfusion rates, but they require intravenous administration and continuous infusions and so are difficult for ambulance services to administer. Zalunfiban (RUC-4) is a novel, subcutaneously administered, GPIIb/IIIa inhibitor specifically developed to facilitate pre-hospital administration, thereby maximizing the chance for early reperfusion. This sub-analysis investigated the incidence of complete reperfusion (TIMI grade 3 flow) before primary PCI in patients treated with zalunfiban on arrival at the catheterization laboratory as a function of the dose of zalunfiban. Material and methods: This was a prospective, single-centre, open-label, phase IIa study designed to assess the pharmacodynamics, pharmacokinetics, and tolerability of zalunfiban in patients with STEMI undergoing primary PCI. Zalunfiban was administered immediately upon arrival at the catheterization lab, which was ∼10–15 minutes before the initial angiogram used to assess TIMI grade flow. Results and conclusion: A total of 27 patients received a weight-adjusted subcutaneous injection of zalunfiban in escalating doses (0.075 mg/kg [ n = 8], 0.090 mg/kg [ n = 9], or 0.110 mg/kg [ n = 10]). Of these, 25 patients were evaluable for angiographic analysis. TIMI flow grade 3 pre-PCI was observed in 1/7, 2/9 and 5/9 patients and showed a dose-related effect ( P trend = 0.04). The ongoing international, phase III, double-blinded, randomized, placebo-controlled, CELEBRATE trial is designed to assess whether a single, ambulance-based pre-hospital injection of zalunfiban results in improved clinical outcome. Funding: This study was supported by CeleCor Therapeutics.